Emperor penguins and the First German South Polar Expedition, 1901–1903: The elusive colony in Posadowsky Bay. (30th April 2021) - Wienecke, Barbara
Abstract: Members of the First German South Polar Expedition (1901– 1903) encountered emperor penguins ( Aptenodytes forsteri ) near their wintering station in the sea ice of Posadowsky Bay, East Antarctica. The penguins appeared to be generally less of scientific interest, but more of a useful resource. Despite the presence of chicks, the men were uncertain about the existence of a breeding colony, and did not record the position of the penguin aggregation they encountered. In later years, only a few sightings confirmed the existence of a colony, and the last ground visit took place in 1960. Based on satellite imagery, a colony appears to exist even now. This paper examines what impact the expedition may have had on this colony, and whether it still exists.